Self-Efficacy as a Determinant of Self-Care Management in Patients undergoing Hemodialysis - Safrudin; Aswan, Srieirsya; Hidayat, Rahmat (Bantayang Omni Cendekia, 2026)
Background: Self-care management is a critical component of treatment for patients undergoing hemodialysis, yet many patients experience difficulties in maintaining optimal self-care behaviors. Self-efficacy has been identified as a key psychological factor that may influence patients’ ability to manage their health effectively. Objective: The purpose of this study was to determine the correlation between self-efficacy and self-care management in patients undergoing hemodialysis. Methods: The research design used was an analytical survey with a cross-sectional study approach with quantitative research methods. Sociodemographic questionnaire, The Hemodialysis Self-Management Instrument (HDSMI-18) questionnaire, and The Chronic Kidney Disease Self-Efficacy (CKD-SE) questionnaire were utilized in this study. The Chi-Square test was employed to analyze the correlation between self-efficacy and self-care management of patients undergoing hemodialysis. Results: A total of 72 respondents participated in this study. Most respondents had high self-efficacy and good self-care management, which were 49 (68.1%) and 54 (75%) respondents, respectively. According to the Chi Square test, there was a significant correlation between self-efficacy and self-care management in hemodialysis patients, with a p-value of 0.001. Conclusion: Self-efficacy is significantly associated with self-care management among patients undergoing hemodialysis, highlighting self-efficacy as an important determinant of self-care management.